Clinical Implications of Tissue Carcinoembryonic Antigen Expression in Ugandan Colorectal Cancer Patients - Richard Wismayer; Julius Kiwanuka; Josephat Jombwe; Emmanuel Elobu; Henry Wabinga; Michael Odida (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
Introduction: Globally colorectal cancer (CRC) is the third most common malignancy. The global incidence of colorectal cancer (CRC) is projected to rise up to 60% in 2030. In Uganda and other resource-deprived countries in Sub-Saharan Africa, colonoscopy is not easily accessible for screening. Therefore, carcinoembryonic antigen (CEA) may have a larger role as a marker for CRC development in these resource-limited settings. The aim of this study was to investigate the incidence of positive CEA in CRC tissue and compare it to clinicopathological features in Ugandan patients. Methods: From 16th September 2019 to 16th September 2021, samples of colorectal biopsy specimens and resected colorectal carcinoma specimens were obtained from patients in Masaka Regional Referral Hospital, Mulago National Referral Hospital, Uganda Martyrs’ Hospital Lubaga and Mengo Hospital. Participants were consecutively recruited from hospitals in central Uganda between 2019-2021, with corresponding formalin-fixed and paraffin-embedded (FFPE) tissue blocks that were included in the CEA analysis. A Data Extraction Form was used to obtain data regarding age, sex, stage, grade of colorectal cancer, and topography. Haematoxylin and eosin sections from FFPE CRC blocks were prepared to establish the grade, lymphovascular invasion (LVI), and histopathological subtype. The CEA molecular marker was analysed using the ABC method for immunohistochemistry. The Pearson chi-square test was used to assess the association between CEA expression and demographic and histopathological variables. The correlation between the CEA biomarker and grade was determined using Spearman’s rank correlation. A p-value of \(\)0.05 was considered statistically significant. Results: The present study evaluated the CRC tissue CEA and the correlation of the tissue staining intensity with the grade, stage, LVI status, topography, and histopathological subtype of CRC. Out of 118 participants, there were 67 male participants and 52 female participants and the median age (SD) for all the participants was 59.9(15.3) years. Compared to stage I, there were 31.4% of CRC tissues stained positively for CEA in stage IV disease and this reached statistical significance (p=0.0101). There were 73.4% CRC tissues with grade II CRC that stained positively for CEA compared to 15.2% CRC tissues with grade I CRC (p=0.0000). There were more AC (85%) participants that stained positively for CEA compared to MAC (5.8%) and SRCC (9.2%) participants (p=0.0000). A positive correlation between tumour grade and CEA expression was found (r=+0.2204) (p=0.0232). Conclusions: In Uganda, increasing CEA intensity in CRC tissues is associated with a poorer grade. High-grade CRC has a higher incidence of lymph node metastasis and a higher CRC CEA tissue expression. Therefore, in Uganda, there is a poorer prognosis for patients expressing high levels of CEA in their colorectal cancer tissue. The number of rectal cancer patients excluded due to neoadjuvant chemoradiotherapy was small and therefore it is unlikely that selection bias was introduced. The effect of neoadjuvant chemoradiotherapy on tissue CEA expression should be explored in future studies.